2020
DOI: 10.3390/nu12061829
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Anxiety and Prefrontal Cortex Glutamatergic Dysregulation Are Long-Term Consequences of Pre-and Postnatal Exposure to Hypercaloric Diet in a Rat Model

Abstract: Both maternal and early life malnutrition can cause long-term behavioral changes in the offspring, which depends on the caloric availability and the timing of the exposure. Here we investigated in a rat model whether a high-caloric palatable diet given to the mother and/or to the offspring during the perinatal and/or postnatal period might dysregulate emotional behavior and prefrontal cortex function in the offspring at adult age. To this end, we examined both anxiety responses and the mRNA/protein expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…29 Some previous studies reported that the implication of malnutrition on brain structures and neurotransmitters responded to anxiety. 30 Differently, no anxiety-like behaviors were observed in the present study, as showed by the behaviors in EPM. This was supported by Fisch' s data.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…29 Some previous studies reported that the implication of malnutrition on brain structures and neurotransmitters responded to anxiety. 30 Differently, no anxiety-like behaviors were observed in the present study, as showed by the behaviors in EPM. This was supported by Fisch' s data.…”
Section: Discussioncontrasting
confidence: 81%
“…All offspring from both groups were fed a standard diet after weaning. Immunostaining was performed to investigate the histological alteration of brain at postnatal days (PNDs) 30 as demonstrated by the decreased ratio of GFAP + /DAPI + at PND 30 (unpaired Student's t test, P CA1 = 0.0025, P DG = 0.0024). However, no differences in neurons or astrocytes were found at PND 60.…”
Section: Maternal Hsd Impairs the Development Of Hippocampal Astrocytes In Offspringmentioning
confidence: 99%
“…In fact, in the present study, we showed that a maternal HFD during pregnancy and lactation reduced mRNA level of Cnr1 in the PFCTX in male but not female adolescent rats compared to that of rats whose mothers were fed on a control diet. Similarly, male animals born from mothers fed on a palatable diet, and who continued with this diet after weaning, exhibited anxiety-like behavior and reduced expression of the eCB system, the main inhibitory retrograde input to glutamate synapses, reflected in a decrease of the Cnr1 in the PFCTX of the offspring at adult age [ 41 ]. In preclinical studies, depressive-like behavior seems to be associated with impaired eCB signalization.…”
Section: Discussionmentioning
confidence: 99%
“…However, six days post-SNL, anxiety- and depression-like behaviors were not completely developed even if SNL-induced aversion was detected ( Suzuki et al, 2007 ; Wu et al, 2019 ). However, the evidence demonstrated that the analyzed anxiety- and depression-related DEGs such as Gria1 ( Rivera et al, 2020 ), Mapk1 ( Sierra-Fonseca et al, 2019 ), Mapk9 ( Thomson et al, 2020 ), and Fkbp5 ( Zannas et al, 2019 ) contributed to anxiety or depression symptoms in rodents. The further study on the gene expression profiles and emotion-related behaviors including anxiety- and depression-like behaviors at the later stage of neuropathic pain should be carried out.…”
Section: Discussionmentioning
confidence: 96%